Functional results of cataract surgery using the phacoemulsification technique "The CADES/O experience - DIANE, Sonassa; Baldé, Abdoul Karim; Inapogui, Campel Balla; Kéita, Abdoulaye; Diawara, Moussa (Jour Med Resh and Health Sci, 2022)
Introduction: The practice of phacoemulsification remains exceptional in low-income countries, unlike in developed countries. The general objective was to study the functional results of cataract surgery using the phacoemulsification technique with posterior chamber implant at CADES/O located at University hospital Center Donka. Material and methods: This was a prospective observational study for three months from 1er July to 30 September 2021. We included in our study all patients who performed cataract surgery per phacoemulsification technique with intra ocular lens (IOL) at CADES/O. Pre and post-operative visual acuity, intra and post-operative complications and factors related to poor outcomes were determined. We classified postoperative visual acuities according to World Health Organisation recommendations into: good (VA ? 3/10), fair (1/10 ? VA ? 3/10) and poor (VA ? 1/10). Results:During the study period, we were able to study the functional results of 159 eyes of the 159 operated patients. The average age was 64.28±12.5 years with extremes from 10 to 92 years. The most affected age group was 60-69 years (35.2%). The male sex dominated with 54.7% against 45.3% and a sex ratio of 1.2. At 30 days post-op without correction, our results were good with 82.4%, average with 14.5% and bad with 3.1%. Intraoperative, early postoperative and late postoperative complications were dominated by posterior capsular rupture with 10.7%, corneal oedema with 64.8% and posterior capsule opacification with 0.6% respectively. Conclusion: At the end of this study, our results show that phaco-E offers a better visual recovery after cataract surgery with nevertheless a rehabilitation time of at least one month. It offers a good level of operative safety with a low complication rate.